Linear scaling electronic structure calculations with numerical atomic basis set - Shang, Honghui; Xiang, Hongjun; Li, Zhenyu; Yang, Jinlong (International reviews in physical chemistry, 2010)
We discuss in this review recent progress, especially by our group, on linear scaling algorithms for electronic structure calculations with numerical atomic basis sets. The principles of the construction of numerical basis sets and the Hamiltonian are introduced first. Then we discuss how to solve the single-electron equation self-consistently, and how to obtain electronic properties via post-self-consistent-field processes in a linear scaling way. The linear response calculation with linear scaling is also introduced. Numerical implementation is emphasized, with some applications presented for demonstration purposes.